2022
DOI: 10.3390/curroncol29110667
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Accuracy of Using Magnetic Seed for Preoperative Non-Palpable Breast Lesions Localization: Our Experience with Magseed

Abstract: In this retrospective study we share our single-center experience using a magnetic seed for the preoperative localization of non-palpable breast lesions. Patients who underwent a preoperative localization with Magseed® (Endomagnetics, Cambridge, UK) placement between 2020 and 2022 were enrolled. Indications to Magseed placement have been established during multidisciplinary meetings prior to surgery and all patients underwent breast-conserving surgery (BCS). 45 patients were included. Magnetic seeds have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Among the different techniques, recently developed magnetic seed localization may be used to aid in this matter. It has been shown to be effective in locating non-palpable breast lesions, with a high success rate and low complication rates (23). However, as in other methods of detection, magnetic seed localization has an associated percentage of positive margins, which can increase the risk of local recurrence, prompting the need for further surgery.…”
Section: Discussion Nd Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different techniques, recently developed magnetic seed localization may be used to aid in this matter. It has been shown to be effective in locating non-palpable breast lesions, with a high success rate and low complication rates (23). However, as in other methods of detection, magnetic seed localization has an associated percentage of positive margins, which can increase the risk of local recurrence, prompting the need for further surgery.…”
Section: Discussion Nd Conclusionmentioning
confidence: 99%
“…After multidisciplinary group discussion, the patients are usually admitted in the morning for imaging evaluation and seed placement by the radiologist, being submitted to surgery during the same day. One of the main advantages associated with magnetic seed as compared to wire for example is the possibility to be implanted several days before the procedure without the associated discomfort and infection risk associated with the latter technique (23). Although our procedure is as abovementioned and the median of patients had the magnetic seed placed in the same day of surgery, some patients had its placement several days earlier benefiting from higher comfort at home in the days before surgery.…”
Section: Discussion Nd Conclusionmentioning
confidence: 99%
“…The most well-studied marker in this category is a 5 × 1 mm long, steel paramagnetic marker (Magseed, Endomag, Cambridge, UK) investigated in multiple cohort studies (Figure 3) [12,57,58]. This device is licensed for both breast and axillary placement, and early studies demonstrated no migration within the breast [59].…”
Section: Magnetic and Paramagnetic Localizationmentioning
confidence: 99%
“…The value of this outcome measure becomes even more apparent in light of the increasing number of technologies that are currently being investigated for the purpose of breast tumor localization. These techniques include magnetic and paramagnetic localization (Magseed [28][29][30][31], Sirius Pintuition [32,33], MOLLI [34], TAKUMI [35]), radiofrequency reflector-based localization (SAVI SCOUT [36][37][38]), radiofrequency identification tags (LO-Calizer [39][40][41]), EnVisio [42]), and stereotactic marking using a carbon suspension [43][44][45]. Due to the lack of solid evidence with regard to clinical effectiveness, none of these investigated techniques have widespread adoption [46].…”
Section: Introductionmentioning
confidence: 99%